High-speed imaging of spray formation and combustion in an optical engine: Effects of injector aging and TPGME as a fuel additive - Zhu, Xinda; Mannazhi, Manu; Palazzo, Natascia; Bengtsson, Per Erik; Andersson, Öivind (Energies, 2020)
High-speed imaging of fuel sprays and combustion is conducted on a light-duty optical engine to investigate the effects of injector aging, with a focus on soot. The spray behaviors of one new and one aged injector are compared using Mie-scattering. In addition to this, the combustion process of a baseline diesel fuel and a blend with TPGME (tripropylene glycol monomethyl ether) are compared using natural luminosity (NL) imaging. TPGME is an oxygenated additive which can be used to reduce soot emissions. X-ray tomography of the two injectors demonstrates that the aging does not lead to significant geometry differences, nor to formation of dense internal nozzle deposits. Both injectors show similar liquid penetration and spreading angle. However, the aged injector shows a prolonged injection and more fuel dribbling after the injection events, leading to a higher injection quantity. The fuel quantity difference shows a larger impact on the NL at low load than the TPGME additive, indicating that the in-cylinder temperature is more important for soot oxidation than oxygen concentration under these conditions. At medium load, the NL is much less sensitive to small temperature variations, while the TPGME is more effiective for soot reduction.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Diesel combustion; Injector aging; Natural luminosity; Spray formation; TPGME